PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT KIAT PANGAN PERSADA - Sheila A Yughi; Arif Siaha Widodo; Arsid Arsid (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The decline in the sales achievement of PT Kiat Pangan Persada during the 2017-2020 period indicates a decrease in employee discipline and motivation to work so that employees do not work with high enthusiasm. The purpose of this study was to determine the effect of work discipline and motivation on employee performance at PT Kiat Pangan Persada. The research method used is a causal associative method with a quantitative approach. The sampling technique used is a saturated sampling technique with a sample of 60 respondents. Data analysis techniques used are classical assumption test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results showed that work discipline had a positive and significant effect on the performance of PT Kiat Pangan Persada employees with a t count > t table or (6,628 > 2,002). Work motivation has a positive and significant effect on the performance of PT Kiat Pangan Persada employees with a value of t count > t table or (6,311 > 2,002). Simultaneously test the hypothesis that work discipline and work motivation have a positive and significant effect on the performance of PT Kiat Pangan Persada employees with a calculated F value > F table or (32,194 > 2,770).